Comparison of parasitological, immunological and molecular methods for the diagnosis of leishmaniasis in dogs with different clinical signs - Moreira, M. A. B.; Luvizotto, Maria Cecília Rui [UNESP]; Garcia, José Fernando [UNESP]; Corbett, C. E. P.; Laurenti, M. D. (Elsevier B.V., 2007)
Aiming to improve the diagnosis of canine leishmaniasis (CanL) in an endemic area of the Northwest region of São Paulo State, Brazil, the efficacy of parasitological, immunological and molecular diagnostic methods were studied. Dogs with and without clinical sips of the disease and positive for Leishmania, by direct parasite identification on lymph node smears and/or specific antibody detection by ELISA, were selected for the study. According to the clinical signs, 89 dogs attending the Veterinary Hospital of UNESP in Aracatuba (SP, Brazil) were divided into three groups: symptomatic (36%), oligosymptomatic (22%) and asymptomatic (22%). Twenty-six dogs from an area non-endemic for CanL were used as negative controls (20%). Fine-needle aspiration biopsies (FNA) of popliteal lymph nodes were collected and Diff-Quick (R)-stained for optical microscopy. Direct immumofluorescence, immunocytochemistry and parasite DNA amplification by PCR were also performed. After euthanasia, fragments of popliteal lymph nodes, spleen, bone marrow and liver were collected and processed for HE and immunohistochemistry. Parasite detection by both HE and immunohistochemistry was specifically more effective in lymph nodes, when compared with the other organs. Immunolabeling provided higher sensitivity for parasite detection in the tissues. In the symptomatic group, assay sensitivity was 75.61% for direct parasite search on Diff-Quick (R)-stained FNAs, 92.68% for direct immunofluorescence, 92.68% for immunocytochemistry and 100% for PCR; the corresponding values in the other clinical groups were: 32, 60, 76 and 96% (oligosymptomatic), and 39.13, 73.91, 100 and 95.65% (asymptomatic). Results of the control animals from the CanL non-endemic area were all negative, indicating that the methods used were 100% specific. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: canine leishmaniasis; Leishmania (Leishmania) infantum chagasi; diagnosis; enzyme-linked immunosorbent assay (ELISA); polymerase chain reaction (PCR); immunohistochemistry